Implementasi Algoritma A* (Star) untuk Menentukan Rute Jarak Terpendek - ., Yukandri; Tryastie, Melisa; Nelda, Lia; Priskila, Ressa; Pranatawijaya, Viktor Handrianus (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 3 (2024): JNATIA Vol. 2, No. 3, Mei 2024DO - 10.24843/JNATIA.2024.v02.i03.p01, 2024)
In this research, the implementation of the A star algorithm is used to find efficient routes, reduce the travel time, and optimize the use of existing road infrastructure at waypoints. The A star algorithm uses the concept of Open List and Close List, which helps to reduce the number of rechecks on the points travelled, thus speeding up the search process. The A star algorithm stops when there are no more points on the open list or when the end point has been determined. This research method uses primary data, which consists of five street locations in Palangka Raya city, as nodes and combines the distance between the street points. The implemented program uses the A Star algorithm to calculate the shortest route and displays the path along with the distance. The purpose of this research is to achieve the shortest route and calculate the distance travelled for the waypoints.